Plumbing Technology - Hall, F. ([S.l.] : Longman Higher Education, 1987)
Together with the companion volume "Plumbing: Cold Water Supplies, Drainage and Sanitation", Fred Hall provides all the necessary knowledge of the principles on which these systems are designed for students of NVQ and CGLI plumbing courses. Key Features: covers the design and installation of gas appliances, oil-firing systems, hot water supply and heating systems. This edition has been updated to include current Bylaws, Building Regulations and Codes of Practice, fully supported by illustrations, tables and calculations. It includes end-of-chapter test questions. Readership: Core: NVQ Plumbing Level 3 and CGLI Plumbing (6030) level 3. Supplementary: NVQ Heating and BTEC NC/D in Building Services Engineering.